The Influence of Self-Talk on Service Learning and Self-Efficacy Improvement to Volleyball Athletes - Makraki Ελευθερία; Zetou Ελένη; Bebetsos Ευάγγελος; Mavromatis Γιώργος (Inquiries in Physical Education and Sport, 2010)
In this study it was examined the effect of self-talk for technique οn serving skill learning on volleyball. Participants were 49 novice female players (M =13.6, SD=.86, and years of experience Μ=2.11, SD=.68). Prior to the initiation of the intervention, participants were randomly assigned into two groups one self-talk group (STG, n = 24) and one control group (TG, n = 25). All athletes followed a four-week practice program, aiming at serving skill learning. The program consisted of two practice units per week, duration of 60 min each. Participants of STG were instructed to use the self-talk (self-talk for technique) loudly before they performed the serving drills (20΄ per unit). Control group received traditional feedback, provided by the instructor. Service performance was assessed by videotaped evaluations in 5 elements of the skill. There were three measurement sessions for field test: a pre-, a post- and a retention test (one week after post-test). ANOVA repeated measures revealed significant interaction between groups and measure. There were also significant interaction between groups and self-efficacy. The results indicated that participants of the STG improved serving skill learning as well as they improved their self-efficacy. In conclusion, the results showed that self-talk improved performance and learning of serving skill of novice female volleyball athletes. Adding to that, athletes improved their self-efficacy.